Presentation - Cardozo Gaibisso, Lourdes (2025)
The field of TESOL (Teaching English to Speakers of Other Languages) is continually evolving, socially, culturally, and pedagogically. In response to these dynamic challenges, teacher professional learning (also called professional development) has evolved alongside the field; though, such professional development tasks have faced criticism for failing to be grounded in specific contexts. For instance, teachers across the globe face challenges in adapting to diverse student backgrounds, addressing differing language proficiency levels, and integrating culturally relevant materials into their instruction. However, their specific contexts (such as urban/rural, socio-economic divides, infrastructure, and policy environments) mediate their experiences and how they imagine possible changes. In this special issue, which features articles from Uruguay, the United States of America, Argentina, Chile, Colombia, and Vietnam, we present models of teacher professional learning, which are sustainable, responsive, and critically oriented with the goal of contributing to the conversation of what kinds of supports work, for whom, and in which contexts.